计算:5a-{-3b+[6c-2a-(a-c)]}-[9a-(7b+c)]
来源:学生作业帮助网 编辑:六六作业网 时间:2025/02/02 13:38:07
计算:5a-{-3b+[6c-2a-(a-c)]}-[9a-(7b+c)]计算:5a-{-3b+[6c-2a-(a-c)]}-[9a-(7b+c)]计算:5a-{-3b+[6c-2a-(a-c)]}-
计算:5a-{-3b+[6c-2a-(a-c)]}-[9a-(7b+c)]
计算:5a-{-3b+[6c-2a-(a-c)]}-[9a-(7b+c)]
计算:5a-{-3b+[6c-2a-(a-c)]}-[9a-(7b+c)]
5a-{-3b+[6c-2a-(a-c)]}-[9a-(7b+c)]
=5a-(-3b+6c-2a-a+c)-(9a-7b-c)
=5a+3b-6c+2a+a-c-9a+7b+c
=-a+10b-6c
计算:5a-{-3b+[6c-2a-(a-c)]}-[9a-(7b+c)]
(a+b-c)^5(a-b-c)^2(c-a-b)^4(c+b-a)^3 计算
计算a^-2b^-2*(-3a^-3c^3)÷6a^-4b^-5
计算:3(a-b)^5c²×2/3(b-a)^4×[-(a-b)²c]
计算:b(3a-2c)(-2c-3a)
计算-2a^3b^2c(a^2b-b^2c-c^a)
c/6a²b + a/8b²c + b/3c²a 计算
5a+3[2b-3(a-b+2c)-(b-c)] 计算
计算:(2b-3c+a)^2
计算 (2a-b+3c)2
已知A=3a-6a+1,B=-2a^2+3,C=4a,计算(B+C)-{A-(B-C)}.
计算(5a-3b)^2+(a+b)(a-b)
5c/6a^2b+7a/8b^2c-b/12a^2c通分计算
已知a:b:c=2:3:5,计算(10a+12b+5c)/(a+b+c)的值
计算:a^3(b+c-d)+a^2b(c+d-a)-a^2c(d+a+b)
1.计算5a/(6a^2c)-7b/(12ac^2)+11c/8a^2b2.计算[y/(x^2-xy)+x(y^2-xy)]/(xy)3.计算{(b-c)/[(a-b)(a-c)]}+{(a-c)/[(b-a)(b-c)]}+{(a-b)/[(c-a)(c-b)]}4.已知3x/(x^2-1)=A/(x+1)+B/(x-1),求A、B的值.
计算:(a-3b-2c)(2c-3b-a)-(-c-2a)^2
(5a+4c+7b)十(5c一3b一6a) 计算